Enhancing the UV/heat stability of LLDPE irrigation pipes via different stabilizer formulations. (13th July 2021) - Porfyris, Athanasios D.; Luyt, Adriaan S.; Gasmi, Soumia; Malik, Sarah S.; Aljindi, Reem M.; Ouederni, Mabrouk; Vouyiouka, Stamatina N.; Pfaendner, Rudolf; Papaspyrides, Constantine D.
Abstract: Herein different stabilizer formulations of linear low‐density polyethylene (LLDPE) against UV‐ and heat‐initiated degradation are described. The project aims at outdoor applications, such as irrigation piping and profiles, in the Middle East desert regions, where long‐term weathering stability due to high temperatures and solar radiation is important. Two UV/heat formulations, without and with carbon black (CB) as pigment, were incorporated into LLDPE by melt compounding. Neat LLDPE and the stabilized compounds were exposed to accelerated UV and heat aging. Morphological analysis through scanning electron microscopy of the UV‐exposed neat LLDPE showed more severe surface cracking compared to the CB‐containing LLDPE, while all stabilized compounds did not show any surface degradation. Crack formation was less visible for the thermally aged samples. A significant decrease in molecular weight (MW) was observed for the neat UV‐exposed LLDPE, while both unpigmented stabilized compounds showed little change in MW. Mechanical properties, thermal analysis, and carbonyl index results supported the morphological results, which confirmed that CB alone was slightly more effective in protecting the LLDPE against UV initiated degradation, but performed worse against thermal initiated degradation. UV1 and UV2 compounds were efficient against both UV‐ and heat‐initiated degradation, with UV1 performing better for unpigmented compounds, and UV2 for the pigmented ones. Abstract :